Storm cursed [compact disc, unabridged] - Briggs, Patricia (Briggs, Patricia. Mercy Thompson novels., 2019)
Mercy Thompson must face a deadly enemy to defend all she loves. The reality is that nothing and no one is safe. As generals and politicians face off with the Gray Lords of the fae, a storm is coming and her name is Death.